Latin American Consensus on management of residual cardiometabolic risk. A consensus paper prepared by the Latin American Academy for the Study of Lipids and Cardiometabolic Risk (ALALIP) endorsed by the Inter-American Society of Cardiology (IASC), the International Atherosclerosis Society (IAS), and the Pan-American College of Endothelium (PACE) (2021)
Hypertension, hyperglycemia, dyslipidemia, overweight, obesity, and tobacco (smoking, chewing, and vaping), together with a pro-inflammatory and procoagulant state, are the main risk factors related to atherosclerotic cardiovascular disease. Objective and methods: A group of experts from the Americas, based on their clinical expertise in cardiology, cardiovascular prevention, and cardiometabolic (CM) diseases, joined together to develop these practical recommendations for the optimal evaluation and treatment of residual CM risk factors in Latin America, using a modified Delphi methodology (details in electronic TSI) to generate a comprehensive CM risk reduction guideline, and through personalized medicine and patient-centered decision, considering the cost-benefit ratio The process was well defined to avoid conflicts of interest that could bias the discussion and recommendations. Results: Residual risk reduction should consider therapeutic options adapt- ed to specific patient needs, based on five treatment objectives: triglyceride-rich lipoproteins, inflammation, impaired glucose metabolism, high blood pressure, and prothrombotic status. Comprehensive control of all CM risk factors should be a priority to deal with this important public health problem and prevent premature deaths. The recommendations in this paper address the evidence-based treatment of CM risk and are intended for clinical application in Latin American countries.